The Effect of Auxin and Cytokinin Hormones on the Growth of Robusta Coffee (Coffea Canephora) Seedlings in the Grafting Propagation Method of Plagiotrop Rootstock Cuttings - Kamilah, Arina Dian; Rosyady, Muhammad Ghufron; Irsyadi, Muhammad Burhanuddin; Subroto, Gatot; Wulanjari, Distiana; Farisi, Oria Alit; Setiyono, S (Proceeding of International Conference on Biology Education, Natural Science, and Technology, 2024)
Robusta coffee is a type of coffee that can be cultivated vegetatively. Grafting cuttings technique is one of the propagarion techniques commonly used in Indonesia. The use of auxin and cytokinin hormones can be used in the coffee seedling phase to support the growth of coffee plants. The puspose of this study was to determine the effect of auxin and cytokinin hormones on the growth of robusta coffee seedling in the cuttings grafting method. The method use was a factorial completely randomized design with 2 factors. Factor 1 is the concentration of auxin hormones consisting of 3 levels, namely A1 (0 ppm), A2 (50 ppm), and A3 (100 ppm). Factor 2 consentration of cytokinin hormone which consists of 3 levels namely S1 (0 ppm), S2 (50 ppm), and S3 (100 ppm). The result were analysed using ANOVA and further test using Duncan Multiple Ranage Test (DMRT). The parameters observed were the percentage of cuttings success, number of leaves, number of shoots, shoot height, shoot diameter, chlorophyll content. The result showed that the provision of 50 ppm auxin and 50 ppm cytokinin had the best trend in the variable number of leaves, shoot diameter and shoot height.